Reducing the Environmental Footprint of Urban Housing in Sub-Saharan Africa: A Case Study of Cameroon - Modeste Kameni Nematchoua; Mbani Menguissa Andre Marie (Buildings, 2025)
This study presents a comprehensive Life Cycle Assessment (LCA) of the NENGOUE residence, a multi-occupancy building located in Yaoundé, Cameroon, over an 80-year lifespan. The analysis encompasses four life cycle phases—construction, use, renovation, and deconstruction—and evaluates twelve environmental impact categories. The results reveal that the use phase contributes overwhelmingly to environmental burdens, accounting for over 96% of total impacts. To mitigate this dominance, two alternative scenarios were assessed: a sustainable transport model and the integration of a photovoltaic system. In the first scenario, environmentally friendly commuting strategies, such as increased walking, cycling, and public transport, led to a 17.10% reduction in greenhouse gas (GHG) emissions. In the second, rooftop photovoltaics offset 69.29% of the building’s electricity needs, resulting in a 26.72% GHG reduction. A third, combined scenario demonstrated the highest environmental gains, achieving a 42.97% reduction in GHG emissions, alongside substantial improvements across other impact categories, including acidification (−38.4%), cumulative energy demand (−28.3%), and photochemical ozone formation (−40.18%). In addition to the environmental benefits, the study highlights the importance of considering social acceptance, behavioral change, and economic feasibility for real-world implementation. The willingness of residents to adopt sustainable mobility practices, cultural preferences, safety concerns, and the initial cost barriers associated with photovoltaic technology are identified as critical factors. These findings underscore the need for integrated strategies that combine technological innovation with inclusive urban planning and stakeholder engagement. The proposed approach demonstrates that aligning environmental measures with local socio-economic realities can significantly enhance the sustainability of residential buildings, contributing meaningfully to climate change mitigation in Sub-Saharan African cities.